Bend it like beckham - Dhami, Narinder; Berges, Paul Mayeda Bindra, Guljit Chadha, Gurinder (Hodder Children's Books London, 2018)
Jess just wants to play football but her wedding-obsessed parents have other ideas so she hides it from them. But when Jess and her friend Jules join a ladies team and get spotted by a talent scout, it all kicks off